2016
DOI: 10.18393/ejss.2016.2.132-138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of composted tobacco waste and farmyard manure applications on the yield and nutrient composition of lettuce (Lactuca sativa L. var. capitata)

Abstract: Article Info Received : 16.10.2015 Accepted : 27.11.2015 The use of organic wastes in agriculture, forestry and land reclamation has been increasingly identified as an important issue for soil fertility, soil conservation and residue disposal. Using organic wastes in agriculture helps not only to dispose these materials economically, but also reduces negative effects on the environment. In the present study, composted tobacco waste (CTW) combined with farmyard manure (FM) at different ratios was applied to Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…The highest and lowest values were obtained from plots with the highest rate (30 t ha -1 ) and plots without any sawdust addition, respectively. Similar results were obtained in many other studies when organic materials were applied (Demir and Gülser, 2015;Delibacak and Ongun, 2016;Alvarenga et al, 2017). This result could be attributed to the high organic matter content of sawdust (approximately 68%) used in the experiment.…”
Section: Effect Of Sawdust Addition On Soil Chemical Propertiessupporting
confidence: 89%
“…The highest and lowest values were obtained from plots with the highest rate (30 t ha -1 ) and plots without any sawdust addition, respectively. Similar results were obtained in many other studies when organic materials were applied (Demir and Gülser, 2015;Delibacak and Ongun, 2016;Alvarenga et al, 2017). This result could be attributed to the high organic matter content of sawdust (approximately 68%) used in the experiment.…”
Section: Effect Of Sawdust Addition On Soil Chemical Propertiessupporting
confidence: 89%
“…Furthermore, the effects were only observable with the 40 t/ha application rate of TSC pointing to a dose-dependent effect. 44 Although Delibacak and Ongun 15 recommended a 1-month waiting period before planting or sowing activities when soil is amended with uncomposted tobacco waste, the present study indicated that a shorter waiting period of at least 1 week may be adequate. A shorter waiting period may reduce opportunities for nutrient loss, thus fostering optimum nutrient utilisation.…”
Section: Oilseed Rape Yield Response To Fertilisationmentioning
confidence: 52%
“…Soil amelioration with tobacco waste (Nicotiana tabacum L.) has been shown to be beneficial in improving the productivity of various horticultural crops including lettuce (Lactuca sativa), spinach (Spinacia oleracea) and tomato (Lycopersicon esculentum). [15][16][17] Further, soil biological and physical properties have also been enhanced by tobacco waste application in other parts of the world. 18,19 Tobacco waste nutrient levels in the range 1.97-2.38% N, 0.21-0.50% P, 0.32-1.03% K and 38-41% C have been documented, 19,20 pointing to its potential value as a nutrient resource.…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of this is the mesolithic composting phase that vermicompost undergoes following thermolithic composting, which causes further disintegration. Vermicompost (Erdal et al 2000) [44] , which produces a substance rich in humic acids, aids in the development of roots and increases plant biomass (Delibacak and Ongun 2016) [37] . Vermicomposting can raise the soil's nitrogen content by 42%, phosphorus by 29%, and potassium by 57%.…”
Section: Effect Of Vermicompost On Soil Fertilitymentioning
confidence: 99%